2004
DOI: 10.1002/cjce.5450820512
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Modeling Studies of Arsenic Removal with Wood Ash from Aqueous Streams

Abstract: Most of the arsenic removal processes are not cost‐effective and/or not efficient in removing As (III). In this research, it was found that Maple wood ash has the potential to adsorb both As (III) and As (V) from contaminated aqueous streams at low concentration levels without any chemical treatment. Static tests showed up to 80% arsenic removal and in various dynamic column tests the arsenic concentration was reduced from 500 ppb to lower than 5ppb. Finally, the ash column was modeled using the surface excess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Removal at pH 4 was significantly higher than that at pH 7 or 10. Maple wood ash without any chemical treatment was also utilized to remediate As(III) and As(V) from contaminated aqueous streams in low concentrations [132]. Static tests removed ≤80% arsenic while the arsenic concentration was reduced from 500 to <5 ppb in dynamic column experiments.…”
Section: Fly Ashmentioning
confidence: 99%
“…Removal at pH 4 was significantly higher than that at pH 7 or 10. Maple wood ash without any chemical treatment was also utilized to remediate As(III) and As(V) from contaminated aqueous streams in low concentrations [132]. Static tests removed ≤80% arsenic while the arsenic concentration was reduced from 500 to <5 ppb in dynamic column experiments.…”
Section: Fly Ashmentioning
confidence: 99%
“…Removal at pH 4 was significantly higher than that at pH 7 or 10. Maple wood ash without any chemical treatment was also utilized to remediate As(III) and As(V) from contaminated aqueous streams in low concentrations [72]. Static tests removed ≤80% arsenic while the arsenic concentration was reduced from 500 to <5 ppb in dynamic column experiments.…”
Section: Blast Furnace Slagmentioning
confidence: 99%
“…Ash is an alkaline material with a pH ranging from 9-13, and due to its high alkalinity characteristics, wood ash has various applications in different sectors as an environmentally friendly alkaline substance. Rahman et al (2004) reported that wood ash was found to be effective arsenic adsorbent from contaminated aqueous streams at lower concentration levels.…”
Section: The Chemistry Of Wood Ashmentioning
confidence: 98%